DIVERSITY AND INTERCULTURAL COMPETENCE FOR SUSTAINABLE COMMUNITY DEVELOPMENT - Marja Nesterova; Agostino Portera; Marta Milani (Baltic Journal of Economic Studies, 2022)
The relevance of the research topic is that modern societies are diverse and face several challenges that appear to threaten sustainable community development. Many of them are related to diversity and intercultural communication issues. The purpose of the article is to determine the main aspects and practical applications of diversity and intercultural competence in the focus of community sustainable development. The objectives are to look through recent publications dedicated to the various aspects of intercultural competence and diversity competence; to analyze and summarize the models of intercultural communication and competence described in recent publications, as well as diversity competences; to formulate the basic principles of diversity management for sustainable development of educational and business communities. Study results. The article outlines the main features of different models of intercultural and diversity competence. The main approaches to intercultural and diversity competence in the educational and business spheres are investigated. A set of key values and key diversity competencies is presented. Part of the study of social cohesion was the change in the parameters of intercultural and diversity competence in a crisis society. Methodology of the research. The theoretical foundations of diversity management are based on a comparative analysis of recent publications on this issue and the results of modern social practice of organizations in the field of diversity management. The methodological and practical foundations of the above research are based on the previous intercultural and social cohesion studies at the National Pedagogical Dragomanov University (now Ukrainian State Dragomanov University). The Social Cohesion Radar Model has been adopted for practical research in the educational community. This made it possible to present some indicators of social cohesion – "acceptance of diversity" and "trust" as key factors for successful communication, social relations, and, consequently, community development. This model provides an understanding of "acceptance of diversity" and "trust" as key components of social cohesion and monitoring their status in different situations of social challenges, including the challenges of the war in Ukraine and the pandemic. A working analogy of the Diversity Radar model for monitoring and assessing diversity intelligence in a community is presented. Practical significance of the research. The study identified the level of acceptance of multicultural diversity in the community and outlined weaknesses for further strengthening with appropriate social and educational tools. The article collects and analyzes various diversity competencies and practical steps to develop diverse and sustainable communities, especially educational ones.